Robert Longo : The Freud Cycle 2000-2004. - Spies, Werner (München : Edition Schellmann München, 2004)
Robert Longo's series of digital pigment prints, The Freud Cycle, draws into focus the Vienna apartment where Freud lived and worked, a scenery in which different historic and cultural layers are present in a merely mystical way. The interior of the Fin de Siècle, the place of birth and activity of the Vienna psychoanalysis, and the gloominess of the crimes of the Nazi period.
Duits
Engels
boek
Keywords: Longo, Robert; Freud, Sigmund